2019
DOI: 10.1039/c9tx00143c
|View full text |Cite
|
Sign up to set email alerts
|

Study of mitochondrial swelling, membrane fluidity and ROS production induced by nano-TiO2 and prevented by Fe incorporation

Abstract: The potential impact of TiO2 and Fe incorporated TiO2 nanoparticles at the organelle level has been reported. The toxicity of the samples on mitochondria isolated from chicken liver tissue has been examined through mitochondrial swelling, membrane fluidity, ROS generation capacity, and activity of complex II. The toxic effect of TiO2 was prevented by incorporating Fe into the TiO2 matrix at different concentrations. The activity of the succinate dehydrogenase enzyme complex was affected and permeabilization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In MCF-7 and HCT-116 cells, N-SNPs increased the swelling of mitochondria and caused damage to their outer and inner membranes as well as their matrix and cristae. This suggests that the mechanism by which N-SNPs are toxic to cells involves their ability to induce oxidative stress via increasing ROS production; specifically, an increase in swelling of mitochondria enhances membrane fluidity and ROS generation and, thus, inhibits the respiration process [ 65 ]. These results were consistent with the data from the antioxidant analysis, which suggested that N-SNPs induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In MCF-7 and HCT-116 cells, N-SNPs increased the swelling of mitochondria and caused damage to their outer and inner membranes as well as their matrix and cristae. This suggests that the mechanism by which N-SNPs are toxic to cells involves their ability to induce oxidative stress via increasing ROS production; specifically, an increase in swelling of mitochondria enhances membrane fluidity and ROS generation and, thus, inhibits the respiration process [ 65 ]. These results were consistent with the data from the antioxidant analysis, which suggested that N-SNPs induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Additional potential sources of ROS include activation of cytoplasmic NADPH oxidases (Bedard and Krause, 2007) and damage to the mitochondrial membrane (Ghosh et al., 2013). With regard to the latter possibility, TiO 2 NPs (< 100 nm) have been shown to be localised in liver mitochondria (Louro et al., 2014) and to induce mitochondrial swelling, promote membrane fluidity and increase ROS generation (Kathawala et al., 2015; Barkhade et al., 2019).…”
Section: Assessmentmentioning
confidence: 99%
“…142 Barkhade et al showed that cells treated with titanium dioxide NPs exhibited swallowing mitochondria and influence the mitochondrial membrane permeability. 143 Also, it was found that Au-NPs increase number of mitochondria and decrease the number of lipid droplets indicating that cells produce more energy in trial to remove the stress caused by NPs. 142 Furthermore, the high incidence of, autophagic vacuoles, endosomes, cytoplasmic vacuoles were observed after treatment cancer cells with Ag-NPs.…”
Section: Killing Strategies Of Nps Against Living Cellsmentioning
confidence: 99%